2020
DOI: 10.1177/0192512120917186
|View full text |Cite
|
Sign up to set email alerts
|

Institutional foundations of global well-being: Democracy, state capacity and social protection

Abstract: This is an article about the foundations of human well-being. It makes two integrated contributions. We first examine well-being around the contemporary world, finding a remarkable correlation between subjective and objective measures and a considerable variation in overall well-being among countries. We then argue that certain institutional conditions have laid the basis for these differences. Integrating insights from several research strands, we outline a new explanatory model of popular well-being that con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
5
0
2
Order By: Relevance
“…Specifically, people living in a country that has high levels of political freedom reported higher levels of happiness and wellbeing (Spruk & Keseljevic 2016). Both democracy and political freedom implies that the government is more likely to devote resources towards achieving higher standards of living, and the leaders are more likely to prioritize goals relevant to human development over others (Cronert & Hadenius, 2021). Thus, consumers will expect their wellbeing to be emphasized and positively transformed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Specifically, people living in a country that has high levels of political freedom reported higher levels of happiness and wellbeing (Spruk & Keseljevic 2016). Both democracy and political freedom implies that the government is more likely to devote resources towards achieving higher standards of living, and the leaders are more likely to prioritize goals relevant to human development over others (Cronert & Hadenius, 2021). Thus, consumers will expect their wellbeing to be emphasized and positively transformed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A large body of research has found that democratic governments put higher priority on safeguarding the population's well-being (e.g. Kahn 2005;Besley and Kudamatsu 2006;Kudamatsu 2012;Flores and Smith 2013;Pieters et al 2016;Bollyky et al 2019;Cronert and Hadenius 2021). Evaluating possible mechanisms behind this effect, Bollyky et al (2019) recently concluded that it was specifically the existence of competitive elections that promoted better health outcomes, likely by improving political leaders' accountability and responsiveness concerning health issues.…”
Section: Democratic Institutions Accountability and Blame Avoidance C...mentioning
confidence: 99%
“…However, while some scholars argue that state capacity and political institutions work synergistically (e.g. Cronert and Hadenius, 2021), others indicate that state capacity improves health and education outcomes also in the absence of democratic institutions (e.g. Hanson, 2015).…”
Section: Hypothesesmentioning
confidence: 99%